Treading on sacred grounds: places of worship, local planning and religious freedom in Australia - Villaroman, Noel G. (Studies in religion, secular beliefs and human rights, 2015)
In Treading on sacred grounds : places of worship, local planning and religious freedom in Australia, Noel Villaroman analyses the spatial or structural constraints to religious freedom as a result of local planning regulations in Australia